An Organizational Change Triggered by a Survey: The Army Air Forces in World War II - Harrell, Thomas W. (Academy of Management Review, 1977)
In this article the author examines how during World War II the United States Army Air Forces (AAF) made use of an attitude survey that brought about what was essentially a process of organizational change. The author discusses how the survey yielded results that showed one third of the enlisted men in the AAF felt they were assigned to the wrong jobs. As a result a reform process what begun with the aim of getting the right men into the right positions. The author discusses the success of the program, noting that in a short period of time individuals who scored high on intelligence tests were moved into positions where they could better serve the AAF.